Sekurytyzacja wzmożonej śmiertelności - Małek, Aleksandra (Extreme Mortality Securitization, 2008)
Extreme mortality risk has been a part of the insurance industry since its beginnings. Natural catastrophes and pandemics are nothing new - humanity since prehistory has had to deal with the destructive force of hurricanes and the ravaging diseases. Analyzes of catastrophic statistics show that nowadays the extreme mortality caused by natural disasters is strictly connected with poorly developed countries - in rich countries thanks to high technological advances and investments in meteorological and hydrological methods there are early prediction systems providing a better chance for evacuation. However, this does not eliminate the extreme mortality risk. The life insurance industry is extremely exposed due to new diseases and terrorism risk with all its forms. Nowadays the insurance sector worldwide is focused on these risks as a consequence of the WTC attacks and the current SARS outbreak. The extreme mortality risk of insurance and reinsurance companies needs to devise new solutions, using mechanisms of capital markets as substitutes for classical reinsurance and retrocession methods. The risk securitization in the life insurance industry is meeting new opportunities. This paper tries to identify the aspects of extreme mortality risk and to examine securitization programmes, focusing on trigger mechanism structures and indices construction.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1197, s. 229-236